Effectiveness of Positive Couple Therapy on Mothers’ Attitudes Toward Their Children with Special Needs - Bolghan Abadi, Mustafa; Niakan, Zhinoos; Alipour Sakhavi, Mohammad (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: Parental attitudes toward their children with special needs are often dual in nature—ranging from affection and appreciation on the one hand, to emotions such as denial or overprotection on the other, which can disrupt the child’s natural psychological development. The aim of the present study was to investigate the effectiveness of positive couple therapy on mothers’ attitudes toward their children with special needs. Materials and Methods: The research method was experimental, using a pre-test/post-test design with follow-up and a control group. From among mothers of children with special needs in Mashhad, 20 participants were selected using convenience sampling and randomly assigned to experimental and control groups (10 participants in each group). To collect data, the Parental Attitude Toward Children with Special Needs Scale (Gunderson, 2002) was used. Descriptive statistics including means and standard deviations were calculated, and inferential statistics were performed using mixed analysis of variance (ANOVA). Findings: The results indicated that the attitudes of mothers who received the intervention toward their children with special needs had significantly improved (p < .05). Conclusion: Based on the results obtained, it can be concluded that positive couple therapy is effective in improving mothers’ attitudes toward their children with special needs in the city of Mashhad.